(untitled) (Comprehensive Journal of Science, 2025)
This research examines the role of socialization in shaping an individual’s personality, considering it a fundamental process that has received considerable attention in both sociological and psychological traditions. The research emphasizes that socialization represents the frame of reference through which an individual acquires their personality traits, values, and behavioral standards, enabling them to interact positively with their social environment. Thus, socialization is a systematic and scientific process that plays a pivotal role in building an individual’s social personality, ensuring the continuity and cohesion of society and contributing to a balance between individual needs and the needs of the group.